Maxillo-mandibular counter-clockwise rotation and mandibular advancement with TMJ Concepts (R) total joint prostheses Part I - Skeletal and dental stability - Dela Coleta, K. E. [UNESP]; Wolford, L. M.; Gonçalves, João Roberto [UNESP]; Santos-Pinto, Ary dos [UNESP]; Pinto, L. P.; Cassano, D. S. (Churchill Livingstone, 2009)
The purpose of this study was to evaluate skeletal and dental stability in patients who had temporomandibular joint (TMJ) reconstruction and mandibular counterclockwise advancement using TMJ Concepts total join, prostheses (TMJ Concepts Inc. Ventura, CA) with maxillary osteotomies being performed at the same operation. All patients were operated at Baylor University Medical Center, Dallas TX, USA, by one surgeon (Wolford). Forty-seven females were studied; the average post-surgical follow-up was 40.6 months. Lateral cephalograms were analyzed to estimate surgical and post-surgical changes. During surgery, the occlusal plane angle decreased 14.9 +/- 8.0 degrees. The maxilla moved forward and upward. The posterior nasal spine moved downward and forward. The mandible advanced 7.9 +/- 3.5 mm at the lower incisor tips, 12.4 +/- 5.4 mm at Point B, 17.3 +/- 7.0 mm at menton, 18.4 +/- 8.5 mm at pogonion, and 11.0 +/- 5.3 mm at gonion. Vertically, the lower incisors moved upward -2.9 +/- 4.0 mm. At the longest follow-up post surgery, the maxilla showed minor horizontal changes while all mandibular measurements remained stable. TMJ reconstruction and mandibular advancement with TMJ Concepts total joint prosthesis in conjunction with maxillary osteotomies for counter-clockwise rotation of the rnaxillo-mandibular complex was a stable procedure for these patients at the longest follow-up.
Keywords: orthognathic surgery; TMJ prostheses; stability